Formulation and Evaluation of Cream of Green Tea Extract and Salicylic Acid for Acne Treatment - Samia Alsawi; Wedad Saleh; Donia Algadaafie; Safa Ali; Alaweya Kamal (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this study is to formulate and evaluate four different formulas of vanishing cream prepared with green tea extract and Salicylic acid as active ingredients. Formulation of four different formulas of vanishing cream by different percentages of Stearic acid, E. wax, Almond oil, Glycerin, and Purified water using different percentages of Potassium hydroxide, all formulations prepared with green tea and Salicylic acid as active ingredients, the formulations were preserved by Phenoxyethanol, and Rose oil was used as flavor, all formulations were evaluated by physical examinations, PH measurement, spreadability test, and viscosity measurements. The current finding showed that the change in a composition and percent of components of cream results in change in physicochemical properties of cream like homogeneity, color appearance, after feel, and washability. The range of pH for formulas was 4.3 to 7.4, viscosity range was found 29000 (F1)– 19000 pa.s (F4) at 10 rpm with shear-thinning behavior of formulations, and spreadability was ranged from 4.90 to 7.06 cm². All formulas were accepted when examined for these properties but F4 was more homogeneous, very moist and soft with rabid washability and it was the lower viscosity and higher spreadability compared to other formulas. According to pH value, F1 and F3 were close to physiological pH of skin more than F4 while pH of F2 is compatible with physiological pH (5.6). The formula F2 was homogeneous, smooth with very good washability, moderate viscosity, and very good spreadability in addition to the compatible pH and we can choose it as an optimum formula that will need further modification and examination to formulate an excellent cream. الهدف من هذه الدراسة هو صياغة وتقييم أربع صيغ مختلفة من كريم التلاشي المحضر بمستخلص الشاي الأخضر وحمض الساليسيليك كمكونات نشطة. صياغة أربع صيغ مختلفة من كريم التلاشي بنسب مختلفة من حامض دهني ، E.wax ، زيت اللوز ، الجلسرين ، والمياه النقية باستخدام نسب مختلفة من هيدروكسيد البوتاسيوم ، جميع التركيبات المحضرة بالشاي الأخضر وحمض الساليسيليك كمكونات نشطة ، تم حفظ التركيبات بواسطة Phenoxyethanol ، وتم استخدام زيت الورد كنكهة ، وتم تقييم جميع التركيبات عن طريق الفحص الفيزيائئ، قياس درجة الحموضة واختبار قابلية الانتشار وقياسات اللزوجة. كما وجدنا في دراستنا لصياغة الكريم ، فإن التغيير في تكوين ونسبة مكونات الكريم يؤدي إلى تغيير في الخصائص الفيزيائية والكيميائية للكريم مثل التجانس ومظهر اللون وبعد الشعور وقابلية الغسل. كان نطاق الأس الهيدروجيني للصيغ 4.3 إلى 7.4 ، وتم العثور على نطاق اللزوجة 29000 (F1) - 19000 pa.s (F4) عند 10 دورة في الدقيقة مع سلوك ترقق القص للتركيبات ، وتراوحت قابلية الانتشار من 4.90 إلى 7.06 سم². تم قبول جميع الصيغ عند فحصها لهذه الخصائص ولكن F4 كان أكثر تجانسا ورطبا جدا وناعما مع قابلية غسل مسعورة وكان اللزوجة المنخفضة وقابلية الانتشار الأعلى مقارنة بالصيغ الأخرى. وفقا لقيمة الأس الهيدروجيني ، كان F1 و F3 قريبين من درجة الحموضة الفسيولوجية للجلد أكثر من F4 بينما يتوافق الرقم الهيدروجيني ل F2 مع الرقم الهيدروجيني الفسيولوجي (5.6). كانت الصيغة F2 متجانسة وناعمة مع قابلية جيدة جدا للغسل ولزوجة معتدلة وقابلية انتشار جيدة جدا بالإضافة إلى درجة الحموضة المتوافقة ويمكننا اختيارها كصيغة مثالية ستحتاج إلى مزيد من التعديل والفحص لصياغة كريم ممتاز.